Estimasi Pengaruh Vaksin DPT pada Kematian Anak: Analisis Diskritif Data Surveilan Demografi dan Kesehatan di Kabupaten Purworejo - Siswanto Agus Wilopo (Berita Kedokteran Masyarakat (BKM), 2008)
Background: Recent  controversial  reports  suggest  that  recipients  of  one  dose  of DTP  vaccine  have  higher mortality  than  children who  have  received  no DTP  vaccine. Those  reports were mainly  derived  from African countries where mortality and malnutrion were  higher  than  Indonesia.Objectives: To  describe  specific  and  non-specific  effects  of DTP  vaccination  on  child mortality  age  1-24 months under  routine vaccination  program  in  Indonesia.Methods: During  period of  January 1  1995  to August 31,  2001  our  longitudinal  surveillance  data at  Purworejo district provided  information on 5647 children below 24 months of age who  received DTP and other vaccinations. The main  outcome measure was  all-cause mortality. Vaccination  status  on DTP, BCG,  and measles were collected  every  90 days  and  recorded  its  time  at  vaccination. Confounding  factors  associated with mortality were  also collected. This  first  report used  descriptive analysis  and a  survival curve  (Kaplan-Meier)  to  examine the  differential of mortality according  to sex  of  the  children and  among vaccinated  and  non-vaccinated  children with DTP, BCG,  and measles vaccines. The second  report will  use  survival  analysis  to  estimate specific  and non-sprecific  effects  of DTP  by  considering  time at  vaccination and  other counfounding  factors.Results: There  is no  sex differential  of mortality among  children  in Purworejo.  A  probability of  dying was  lower in  the  children vaccinated with DTP  vaccine compared with  those  not vaccinated DTP. Simmilarly,  vaccinated children with  BCG  and measles  have  lower mortality  compared  to  unvaccinated  children.  There  is  strong indication  that BCG and measles  have  stronger protected  effects  to  risk of  dying  than DTP.Conclusion:   The study showed  lower mortality among children who  received DTP, BCG, and measles vaccines compared  those unvaccinated.  There were  not enough  evidences  to  change current  vaccination policy  because DTP was not  associated with  any harmful  effect  among  girls.Keywords: non-specific  effects, DTP  vaccine–child  survival-  Kaplan Meier’s Curve